2004
DOI: 10.1111/j.1532-5415.2004.52104.x
|View full text |Cite
|
Sign up to set email alerts
|

Declining Executive Control in Normal Aging Predicts Change in Functional Status: The Freedom House Study

Abstract: ECF is a significant and independent correlate of functional status in normal aging. Traditional dementia case finding is likely to underestimate cognition-related disability. Neither a normal baseline MMSE score nor stable MMSE scores over time preclude functionally significant changes in ECF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
216
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(239 citation statements)
references
References 37 publications
18
216
3
2
Order By: Relevance
“…It also provides evidence that an EF battery of tests can be administered to this population in their homes based on the number of subjects who were willing to complete these measures as previously reported. Consistent with the ED literature, this study found that individuals with high MMSE scores may test positive for scores consistent ED [12] . As previously mentioned, the MMSE is a global screen for cognition (i.e.…”
supporting
confidence: 76%
“…It also provides evidence that an EF battery of tests can be administered to this population in their homes based on the number of subjects who were willing to complete these measures as previously reported. Consistent with the ED literature, this study found that individuals with high MMSE scores may test positive for scores consistent ED [12] . As previously mentioned, the MMSE is a global screen for cognition (i.e.…”
supporting
confidence: 76%
“…Alternately, cognition has been measured between dialysis treatments using a battery of neuropsychiatric tests (5) which, although very sensitive measures, are infeasible for adminstration by clinicians during the dialysis treatment. By using the EXIT25 in addition to the MMSE, we were able to capture executive dysfunction, a facet of cognition associated with the ability to independently perform instrumental activities of daily living (26). The high rate of completion of the SPPB, a test of physical performance that has been shown to be predictive of mortality and nursing home placement (27), stands in contrast to prior studies utilizing alternative physical performance measures, which had substantially higher rates of incomplete assessments (28,29).…”
Section: Discussionmentioning
confidence: 59%
“…First, executive dysfunction may play a particularly important role in the progression of disability. For example, Royall (Royall, 2006;Royall et al, 2004, Royall et al,2005 argues for the central role of executive dysfunction in causing functional disability and in the conversion of MCI to dementia. Perhaps executive functions, because of their role in regulating and coordinating other mental functions, organizing behavior and generating responses, play a central role in a variety of everyday activities.…”
Section: Discussionmentioning
confidence: 99%